Marketing Skills and Sanitary Status of Retail Meat Shops In relation to Butchers’ Educational Background in Maharashtra - Waghamare, R. N.; Londhe, S. V.; Ajabe, S. S.; Khobe, V. V.; Deshmukh, V.V. (Indian Journal of Extension Education, 2022)
In India meat production is an unorganized business, although, ideally the butchers should possess basic education along sound understanding of sanitary practices and have standard infrastructure promoting meat business. A study was carried out in year 2021 to study the impact of butchers’ education on marketing skills and sanitary status of retail meat shops. The data was collected on 118 butchers’ shop through interview method. The study revealed that 42.37 per cent of the respondents had completed their secondary education with average age between 25-35 years. The study showed that 67.80 percent respondents running butchery as family business without undergoing any professional training. Butcher shops (42.37%) sales both chicken and mutton of which 68.64 and 80.51 per cent shops had registration with FSSAI and local body, respectively. COVID-19 has not affected meat business as compare to various religious festivals. Respondents (65.25%) believed that online marketing by corporate companies may not affect local meat business. Majority of butchers (85.59%) were unaware about modern slaughtering equipments. Considering the findings, a comprehensive skill development programme may be initiated on hygienic meat production.
Keywords: Butchers shop; Education; Sanitary status; Skill development; COVID-19